Analisis Hukum terhadap Tindak Pidana Pencurian Identitas di Indonesia - Diyu Sulaeman; Anyelir Puspa Kemala (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
The rapid development of technology has led to the emergence of new crimes, one of which is the theft of personal data. Crimes of personal data theft in Indonesia often occur every year, this is due to weak supervision and lack of public education regarding personal data protection, especially according to data from the Ministry of Communication and Information, there are still many regional communities who still do not fully understand digitalization regarding data protection. In the PDP regulation, there are derivative regulations that have not been made by the government, which makes the effectiveness of handling personal data theft still not optimal. From this, problems are obtained, namely how the mode of crime of personal data theft and the extent to which the government prepares to educate the digital community and how legal protection for victims applies in Indonesia. With these two problems, the research method used is juridical normative research. The results of this method show that the perpetrators without asking permission can obtain the personal data of the victims through social media, illegal online loans and lottery scams. In Indonesia itself there is legal protection that regulates, namely in Law. No. 27 of 2022 concerning personal data protection, although the PDP regulation itself creates a new task for the government to make its regulatory delegation..